Peran Multimedia untuk Pembelajaran dan Berbagai Bidang di Sekolah Dasar - Syamsiani Syamsiani (Pusat Riset dan Inovasi Nasional, 2022)
The purpose of this study was to determine the role of multimedia for learning and various fields in elementary schools. Based on the purpose of this study, qualitative research methods are considered to be the appropriate method to be used. Qualitative method is a method that emphasizes research to examine the complex details of a subject, examine the relationship between social events, cultural phenomena and society through life, experiences, behavior, perspectives, points of view, emotions and feelings. The benefits of educational media in the learning process include laying concrete foundations in thinking to reduce 'verbalism', increase student interest, make lessons more fun so that it has an impact on more satisfying learning outcomes. The advantage of multimedia in interactivity is that this media is inherently able to force users to interact with the material both physically and mentally.